Product Effects of Shape Risk Perception on Hand Sanitizer Packaging - Huarng, Shy-Peih (VCD: Journal of Visual Communication Design, 2025)
This study examined curved and angular shapes to explore the risk perception of shapes in product design. Risk perception and product effect were analyzed based on three types of hand sanitizer logos and three packaging shapes. The results in Experiment 1 showed that circular and triangular logos were more effective than square logos in increasing consumers' risk perception. In Experiment 2, no difference in risk perception was observed among the curved, curved/angular, and angular package shapes. In Experiment 3, the circular logo had a better product effect than square and triangle logos. Moreover, curved and curved/angular packaging shapes had a better product effect than angular, suggesting that the curved shape did have a better effect. Therefore, when consumers judge hand sanitizer products, curved shapes representing warmth and friendliness were more likely to increase risk perception and product effect than angular shapes that exhibited a sense of power or threat. The results demonstrate people's innate preference for curved shapes, as well as the impression of curved shapes exhibiting a sensation of bubbles or flowing water when scrubbing lotion using hand sanitizer. The findings suggest that the design of a hand sanitizer logo and package should contain non-threatening curved shapes that could convey positive feelings through warm and friendly imagery.